POP REVIEW Sleep Call (2023): A Captivating Dive into the Dark Realities of Modern Life - Bensa, Cheryl Pricilla (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2024)
Sleep Call (2023), a psychological thriller directed and written by Fajar Nugros, has garnered attention for its captivating narrative and exploration of contemporary societal issues. The film skillfully intertwines a gripping narrative with a profound examination of contemporary issues, offering compelling commentary on the complexities of human relationships, the evolving nature of human interaction in the digital age, and the societal implications of technological advancements. Additionally, the film's portrayal of hyperrealism, class differences, and the impact of capitalism on mental health provides a thought-provoking reflection on the challenges faced by individuals in navigating a rapidly changing society. Furthermore, while the film's focus on gender dynamics and mental health is commendable, its portrayal of these issues could be more balanced. There seems to be a tendency to stereotype female characters as victims or perpetrators of mental illness, which may perpetuate harmful stereotypes rather than challenge them. A more nuanced approach that explores the complexities of these issues beyond gender binaries would add depth to the film's thematic exploration.